Analisis Kinerja Simpang Tak Bersinyal Jalan Raya Dramaga-Bubulak Bogor, Jawa Barat - Listiana, Novi; Sudibyo, Tri (Departemen Teknik Sipil dan Lingkungan IPB, 2019)
The potential of traffic problems at non-signal intersection relatively higher and more complex than signalized intersection. Intersection of Dramaga-Bubulak street has no signal and is one of the intersection with high level mobility. The research objectives were to analysis the performance of actual conditions and alternatives strategies to improve intersection performance as well as to know the influence of one way traffic system on intersection performance. The results showed that the volume of traffic passing the intersection were 3816 passenger car unit (pcu)/hour at peak hour with degree of saturation (DS) of 0.85 and delay on the intersection was 14.41 sec/pcu so the intersection service level was B. The service level of intersection was good, so the research analyzed three alternatives strategies to decrease DS value. Performance analysis of traffic showed that alternatives I was the best model alternative condition, because application of one way traffic system on outer ring Bubulak would decreased the service level of Dramaga-Bubulak street.Key words: intersection, non-signal, street